Engineering a Decorin Surface Coating and Evaluating the Role of Decorin in the Foreign Body Response to Implants - Sylvester, Marisa (My University, 2013)
Encapsulation of medical devices after implantation leads to reduced functionality and device failure of long term implants. To improve healing around implants, and allow long-term implant functionality, the prevention of fibrous encapsulation is necessary. One of the key players in the development of fibrosis is the pro-fibrotic cytokine transforming growth factor beta, whose activity can be neutralized by the proteoglycan decorin, a natural inhibitor of fibrosis. Decorin has demonstrated reduced fibrosis and improved outcomes in numerous models of fibrotic disease and scar tissue formation and thus its ability to reduce fibrous encapsulation around an implant was evaluated. In this work, a novel decorin surface coating was created, characterized, and evaluated as a method for local delivery of decorin to an implant site. In order to rapidly and inexpensively screen and optimize novel therapies for fibrous encapsulation, the chick chorioallantoic model was evaluated as an alternative to standard rodent implantation models. This model was less effective and more restrictive than rodent implant models and thus further evaluation of decorin was carried out in rodent models. Fibrous encapsulation and angiogenesis surrounding decorin-coated and uncoated implants were evaluated in a subcutaneous implant model and found to be similar between the two groups. To further evaluate the therapeutic value of decorin against fibrous encapsulation, a cell-based decorin delivery implant model was developed. This model combined porous polymer implants with a smooth muscle cell-based overexpression system to deliver decorin continuously at an implant site. Decorin overexpression demonstrated no differences in capsule thickness, density, angiogenesis or macrophage infiltration at the implant site demonstrating that decorin would not be a promising therapeutic for inhibiting the FBR, though it has been shown to hold promise in other pathological models of fibrosis. This work provides a novel decorin surface coating that holds potential for use in tumor models and further demonstration for the broad applicability of a collagen affinity coating. Further, a model for delivering molecules of interest at an implant site and evaluating effects on the foreign body response was developed in this work. This model provides an effective method for evaluating future therapies for fibrous encapsulation.
Thesis (Ph.D.)--University of Washington, 2012
Keywords: Collagen affinity coating; Decorin; Fibrous encapsulation; Foreign body response; Surface modification; Biomedical engineering; Bioengineering